1995
DOI: 10.1016/s0022-3913(05)80185-4
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular leakage beneath full cast crowns. Part I: The diffusion of lipopolysaccharide and dextran

Abstract: Fifteen extracted molars were prepared for crowns. Crowns with access ports (one facial, one lingual) were cast in gold. Teeth and crowns with filters inserted into the ports were immersed in solutions of different concentrations of labeled and unlabeled macromolecules (fluorescein isothiocyanate-dextran, tetramethylrhodamine isothiocyanate-lipopolysaccharide [LPS], unlabeled LPS) and were evaluated for leakage. Retrieved filters were analyzed with fluorescent microscopy. At 10 micrograms/ml, only LPS leaked b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 55 publications
0
1
0
2
Order By: Relevance
“…Teeth with gutta-percha root-end fills have been shown to permit leakage of LPS, as shown by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis (20). Conventional fluorescence microscopy has shown that rhodamine-B-labeled LPS leakage occurs under cemented crowns, but the sensitivity of conventional microscopy for detecting the fluorescent tracer has not been adequate (21).…”
mentioning
confidence: 99%
“…Teeth with gutta-percha root-end fills have been shown to permit leakage of LPS, as shown by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis (20). Conventional fluorescence microscopy has shown that rhodamine-B-labeled LPS leakage occurs under cemented crowns, but the sensitivity of conventional microscopy for detecting the fluorescent tracer has not been adequate (21).…”
mentioning
confidence: 99%
“…A multiplicidade de estudos na literatura acerca da avaliação da microinfiltração corrobora para a inexistência de um modelo ideal 3,18,29,44,48,51,53,60 11,12,13,18,25,29,31,38,44,66,79,104,106,110 não contribui para uma análise qualitativa . 8,61,79,104,107,108,120,127,128,129…”
Section: Microinfiltração Marginalunclassified
“…Uma das maneiras utilizadas para verificar tal relação consiste na avaliação da microinfiltração marginal em função da penetração de um corante na interface dente-cimento-restauração. Porém, estudos "in vitro" ou "in vivo" mostram resultados variados entre cimentos e materiais restauradores devido a falta de padronização do corante, tempo de aplicação, técnica de avaliação empregada, presença ou não de ciclagem térmica e ou mecânica, estabelecimento de escores variados de penetração e do tipo de análise realizada na interface dente-cimento (quantitativa ou qualitativa) 11,12,13,27,34,35,43,61,66,92,97,106,107,120,127,128,141 . Como consequência, muitas dúvidas e contradições têm sido apontadas na literatura em função da dificuldade de se obter resultados semelhantes de microinfiltração, tanto "in vivo" como "in vitro".…”
Section: Introdução Introduçãounclassified